Language of fear : a critical discourse study of presidential speeches - Al-Rikaby, Ali Badeen Mohammed; Naser, Hayder S.; Tan, Debbita Ai Lin (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper examines the issue of Iran’s nuclear weapons (INWs); specifically, how the issue is contextualized in political speeches by two world leaders. The presidents, of the United States of America (Donald Trump) and Iran (Hassan Rouhani), present us with contrastive rhetoric and in this paper, we compared their descriptions of INWs. In this critical discourse analysis (CDA) study, we also sought the possible reasons for differences between their descriptions. The selected corpus are Trump’s 2018 speech on Iran’s nuclear weapons program at the United National General Assembly (UNGA) and Rouhani’s 2017 speech on the same issue at the UNGA. These speeches were chosen because of their stance categories and degrees of subjectivity. Jäger’s (2001) CDA model is employed for the purpose of linguistic and contextual analyses. Additionally, Toulmin’s (2003) argumentative models are employed to identify the linguistic tools in both speech texts. The findings reveal contrastive topoi between the descriptions made by the two presidents. Essentially, Trump described INWs as posing a threat to Americans, global peace, and security. Rouhani, meanwhile, reclassified the meaning of INWs, steering it away from the realm of phobia and extending it to include the topoi of self-defense. The key implication here is this: world leaders do propagandize ideologies regardless of the effects of war, and this can be achieved by employing the language of fear for discourse is the crux of political jousting and of power relations.